An image encryption algorithm based on a hidden attractor chaos system and the Knuth–Durstenfeld algorithm - Wang, SiCheng; Wang, ChunHua; Xu, Cong (Optics and lasers in engineering, 2020)
•First, a hidden attractor chaos system is used to encrypt digital image. Compared to self-excited attractor, hidden attractor's attracting basin does not intersect with any small neighborhoods of the equilibria. It is difficult for attackers to reconstruct the attractor by finding equilibrium points.•Second, Knuth–Durstenfeld algorithm has good randomness. At the same time, Knuth–durstenfeld algorithm can reduce the time complexity and the space complexity of the permutation while achieving good permutation effect. Chaotic systems have been widely applied in digital image encryption due to their complex properties such as ergodicity, pseudo randomness and extreme sensitivity to their initial values and parameters. An image encryption algorithm based on a hidden attractor chaos system and Knuth–Durstenfeld algorithm is proposed. First, a hidden attractor chaos system is used to encrypt digital image. Compared to a self-excited attractor, the hidden attractor's attracting basin does not intersect with any small neighbourhoods of the equilibria. It is difficult for attackers to reconstruct the attractor by finding equilibrium points. Therefore, the hidden attractor chaotic system is difficult to decrypt. Meanwhile, the hidden attractor chaos system is very sensitive to initial values and parameters. Second, the Knuth–Durstenfeld algorithm has good randomness. In addition, the Knuth–Durstenfeld algorithm can reduce the time complexity and the space complexity of the permutation while achieving good permutation effects. Thus, Knuth–Durstenfeld algorithm is used to permutate the digital image. Finally, DNA sequence operations are used to diffuse image pixels values. Some experimental analyses have been applied to measure the new scheme, and the experimental results illustrate the scheme possesses better encryption performances. This method can be applied in secure image communication fields.